Antioxidant and In Vitro Preliminary Anti-Inflammatory Activity of Castanea sativa (Italian Cultivar "Marrone di Roccadaspide" PGI) Burs, Leaves, and Chestnuts Extracts and Their Metabolite Profiles by LC-ESI/LTQOrbitrap/MS/MS - Antonietta Cerulli; Assunta Napolitano; Jan Hošek; Milena Masullo; Cosimo Pizza; Sonia Piacente (MDPI AG, 2021)
The Italian "Marrone di Roccadaspide" (Castanea sativa), a labeled Protected Geographical Indication (PGI) product, represents an important economic resource for the Italian market. With the aim to give an interesting opportunity to use chestnuts by-products for the development of nutraceutical and/or cosmetic formulations, the investigation of burs and leaves along with chestnuts of C. sativa, cultivar "Marrone di Roccadaspide", has been performed. The phenolic, tannin, and flavonoid content of the MeOH extracts of "Marrone di Roccadaspide" burs, leaves, and chestnuts as well as their antioxidant activity by spectrophotometric methods (1,1-diphenyl-2-picrylhydrazyl (DPPH), Trolox Equivalent Antioxidant Capacity (TEAC), and Ferric Reducing Antioxidant Power (FRAP) have been evaluated. Furthermore, a cell-based antioxidant in vitro test along with in vitro assays for the evaluation of the ability to reduce nuclear factor-kappa B (NF-κB) activation and nitric oxide (NO) production have been carried out. In order to identify the secondary metabolites responsible for the high phenolic content and the strong antioxidant activity shown by leaves and burs extracts, and to highlight the differences between their chemical composition, the analysis of the metabolite profile of the MeOH extracts obtained from both by-products and chestnuts by liquid chromatography coupled to electrospray ionization and multiple-stage linear ion-trap and Orbitrap high-resolution mass spectrometry (LC-(-)ESI/LTQOrbitrap/MS/MS) has been performed. LC-MS analysis allowed the identification of different classes of specialized metabolites including hydrolyzable tannins, flavonoids, ellagic acid and phenol glucoside derivatives, and triterpenoids as well as polar lipids. Our results show how the antioxidant activity of the extracts can be correlated to their high tannins and flavonoids content while polar lipids occurring in the MeOH extract of the leaves could contribute to determining its higher anti-inflammatory activity.